Use of dental practices for the identification of adults with undiagnosed type 2 diabetes mellitus or non‐diabetic hyperglycaemia: a systematic review. Issue 9 (14th June 2020) - Yonel, Z.; Cerullo, E.; Kröger, A. T.; Gray, L. J.
Abstract: Aim: Type 2 diabetes is a growing global challenge. Evidence exists demonstrating the use of primary care (non‐hospital based) dental practices to identify, through risk assessments, those who may be at increased risk of type 2 diabetes or who may already unknowingly have the condition. This review aimed to synthesize evidence associated with the use of primary care dental services for the identification of undiagnosed non‐diabetic hyperglycaemia or type 2 diabetes in adults, with particular focus on the pick‐up rate of new cases. Method: Electronic databases were searched for studies reporting the identification of non‐diabetic hyperglycaemia/type 2 diabetes in primary care dental settings. Returned articles were screened and two independent reviewers completed the data‐extraction process. A descriptive synthesis of the included articles was undertaken due to the heterogeneity of the literature returned. Results: Nine studies were identified, the majority of which utilized a two‐stage risk‐assessment process with risk score followed by a point‐of‐care capillary blood test. The main barriers cited were cost, lack of adequate insurance cover and people having previously been tested elsewhere. The pick‐up rate of new cases of type 2 diabetes and non‐diabetic hyperglycaemia varied greatly between studies, ranging from 1.7% to 24% for type 2 diabetes and from 23% to 45% for non‐diabetic hyperglycaemia, where reported. Conclusion: This review demonstrates that although it appears there may be benefit in using the dental workforce to identify undiagnosed cases of non‐diabetic hyperglycaemia and type 2 diabetes, further high‐quality research in the field is required assessing both the clinical and cost effectiveness of such practice. (Prospero Registration ID: PROSPERO 2018 CRD42018098750). What's new?: There is an established association between periodontitis and type 2 diabetes. Different populations exhibit different attendance patterns with different healthcare professionals. We found that primary care dental settings can be used to successfully identify previously undiagnosed cases of non‐diabetic hyperglycaemia and type 2 diabetes. The potential early detection of non‐diabetic hyperglycaemia/type 2 diabetes allows for instigation of either prevention strategies or earlier management, which may prove clinically and cost‐effective.